2005
DOI: 10.5194/acp-5-3357-2005
|View full text |Cite
|
Sign up to set email alerts
|

Reactive and organic halogen species in three different European coastal environments

Abstract: Abstract. We present results of three field campaigns using active longpath DOAS (Differential Optical Absorption Spectroscopy) for the study of reactive halogen species (RHS) BrO, IO, OIO and I 2 . Two recent field campaigns took place in Spring 2002 in Dagebüll at the German North Sea Coast and in Spring 2003 in Lilia at the French Atlantic Coast of Brittany. In addition, data from a campaign in Mace Head, Ireland in 1998 was partly re-evaluated. During the recent field campaigns volatile halogenated organic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
129
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 107 publications
(137 citation statements)
references
References 52 publications
7
129
1
Order By: Relevance
“…Butz et al: Inorganic iodine in the tropical UT/LS observed regularly in the form of IO radicals in the lower troposphere with concentrations of several ppt (e.g. Frieß et al, 2001;Peters et al, 2005;Zingler and Platt, 2005;SaizLopez et al, 2006SaizLopez et al, , 2007bRead et al, 2008). Only recently, space-borne observations confirmed enhanced levels of IO near coastal Antarctica (Saiz-Lopez et al, 2007a;Schönhardt et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Butz et al: Inorganic iodine in the tropical UT/LS observed regularly in the form of IO radicals in the lower troposphere with concentrations of several ppt (e.g. Frieß et al, 2001;Peters et al, 2005;Zingler and Platt, 2005;SaizLopez et al, 2006SaizLopez et al, , 2007bRead et al, 2008). Only recently, space-borne observations confirmed enhanced levels of IO near coastal Antarctica (Saiz-Lopez et al, 2007a;Schönhardt et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Measurements in marine boundary layer air indicate that background CH 3 I concentrations range between 0.1 ppt and 2 ppt (Butler et al, 2007;Yokouchi et al, 2008) with higher values reported from North Atlantic coastal source regions (e.g. Peters et al, 2005). Following emission by certain types of algae, molecular iodine (I 2 ) has been identified as an inorganic source of IO x in the coastal boundary layer (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Observations of BrO and IO radicals within the MBL have demonstrated widespread impacts on atmospheric composition and chemistry (Alicke et al, 1999;Sander et al, 2003;Leser et al, 2003;Saiz-Lopez and Plane, 2004;SaizLopez et al, 2004SaizLopez et al, , 2006Peters et al, 2005;Whalley et al, 2007;Mahajan et al, 2010a;Commane et al, 2011;Dix et al, 2013;Gomez Martin et al, 2013;Le Breton et al, 2017), including significant effects on HO x concentrations and on the HO 2 : OH ratio in coastal and marine locations (Bloss et al, 2005a(Bloss et al, , 2010Sommariva et al, 2006;Kanaya et al, 2007;Whalley et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…[15] Only limited work at other sites that support Laminaria digitata has been performed and have only assessed precursor gases. [23] The work at Cape Grim indicates that further work is required at other locations and on other macro-algae to better understand the global importance of the processes identified at Mace Head.…”
mentioning
confidence: 99%